Influence of Emotion Regulation Difficulties on Adaptation to University Life in First-Year Students - Arias, Camila Belén (2026)
Entering university represents a period of profound change that requires a process of personal, academic, social, and institutional adaptation. In this context, emotion regulation (ER) plays a central role in coping with new demands, and difficulties in this domain have been associated with less favorable adjustment to the university environment. The aim of this study was to analyze the influence of ER difficulties on adaptation to university life among first-year students enrolled in the Faculty of Psychology at a public university in Argentina. A non-experimental, cross-sectional, predictive design was used. The sample consisted of 208 regular students (i.e., formally enrolled first-year students actively attending courses), who completed the Difficulties in Emotion Regulation Scale (DERS) and the Student Adaptation to College Questionnaire (SACQ-PE). The results showed that, with the exception of social adaptation, which was only associated with limited access to ER strategies, the remaining dimensions of adaptation exhibited inverse relationships with all ER difficulties. Furthermore, lack of emotional clarity, limited access to emotion regulation strategies, and difficulties in engaging in goal-directed behavior emerged as significant predictors of university adjustment, with differential effects depending on the adaptation dimension considered. In conclusion, these findings highlight the relevance of emotional processes during the university transition and underscore the need to design interventions aimed at strengthening ER skills in first-year students.